Agronomic and molecular characterization of Chloris gayana cultivars and salinity response during germination and early vegetative growth - Ribotta, Andrea N. (2019)
Fil: Ribotta, Andrea N. Instituto Nacional de Tecnología Agropecuaria (INTA). Centro Regional Córdoba. Instituto de Fisiología y Recursos Genéticos Vegetales. Centro de Investigaciones Agropecuarias, Instituto Nacional de Tecnología Agropecuaria (IFRGV-CIAP). Córdoba, Argentina.